Change in wild-oyster assemblages of Port Stephens, NSW, Australia, since commencement of non-native Pacific oyster (Crassostrea gigas) aquaculture - Bishop, MJ; Krassoi, FR; McPherson, RG; Brown, KR; Summerhayes, SA; Wilkie, EM; O'Connor, WA (2010)
Proliferation of species introduced for aquaculture can threaten the ecological and economic integrity of ecosystems. We assessed whether the non-native Pacific oyster, Crassostrea gigas, has proliferated, spread and overgrown native Sydney rock oysters, Saccostrea glomerata, in Port Stephens, New South Wales (NSW), Australia, following the 1991 decision to permit its aquaculture within this estuary. Sampling of seven rocky-shore and four mangrove sites immediately before (1990), immediately after (1991-1992) and nearly two decades after (2008) the commencement of C. gigas aquaculture did not support the hypotheses of C. gigas proliferation, spread or overgrowth of S. glomerata. The non-native oyster, uncommon immediately before the commencement of aquaculture, remained confined to the inner port and its percentage contribution to oyster assemblages generally declined over the two decades. C. gigas populations were dominated by individuals of <40-mm shell height, with established adults being rare. Only at one site was there an increase in C. gigas abundance that was accompanied by S. glomerata decline. The failure of C. gigas in Port Stephens to cause the catastrophic changes in fouling assemblages seen elsewhere in the world is likely to reflect estuarine circulation patterns that restrict larval transport and susceptibility of the oysters to native predators. © 2010 CSIRO.